THE ROLE OF INTERNAL COMMUNICATION IN ACTIVATING KNOWLEDGE MANAGEMENT PROCESSES: A STUDY OF THE OPINIONS OF A SAMPLE OF PROFESSORS AT ALGERIAN UNIVERSITIES - Sarra LAMAMRA; Nour ELHouda SETIFI; Fatma MAHBOUB (Modern Management Review)
The study aimed to investigate the role of internal communication in enhancing knowledge management processes from the perspective of university professors at Algerian universities. An electronic questionnaire was distributed to university professors across various Algerian universities via social media and email, resulting in 115 analyzable forms. Using the SmartPLS V4 program, structural equation modeling was used to examine these shapes. The analysis yielded several key findings, most notably the presence of a positive and moderate role of internal communication across all knowledge management procedures, such as the production, archiving, sharing, and application of knowledge. The study also recommended delving deeper into the importance of digital transformation and its mechanisms for activating internal communications and their significance in knowledge management processes across different contexts.